Development of Gaple Card Media "Smart Fathers Raise Children" as an Educational Media for Fathering in Early Childhood - Irma Yuliantina; Nur Riska; Dhea Yuwono Putri; Karima Salihanisa; Syifa Andina; Dwi Purwestri Sri Suwarningsih; Yuli Yana; Lucy Herny (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2026)
Father involvement in early childhood care plays a crucial role in supporting children's socio-emotional development, health, and well-being. However, father participation in parenting education activities is still relatively limited, partly due to the lack of practical, contextual, and character-appropriate learning media. This study aims to develop and test the feasibility of the Gaple Card educational game "Smart Fathers Raise Children" as a means of family parenting education based on local culture. The study used a Research and Development (R&D) approach with the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The media was developed by modifying the traditional Gaple game and incorporating parenting messages sourced from the BKB Emas Module of the National Population and Family Planning Board (BKKBN). The trial was conducted with groups of fathers in Depok City and North Central Timor Regency (TTU) with facilitator assistance. The evaluation results showed that the media achieved a feasibility level of 96.61%, categorized as very feasible, and reviewed in terms of appearance, message content, ease of use, and usefulness. These findings indicate that the Gaple Card “Smart Fathers Raising Children” is effective as an interactive, non-patronizing, and relevant parenting education media for fathers, and has the potential to be used in the BKB Emas program, PAUD units, integrated health posts (posyandu), and various community-based parenting activities involving fathers.